2014
DOI: 10.1080/03323315.2014.982346
|View full text |Cite
|
Sign up to set email alerts
|

‘Ours is not to reason why, just invert and multiply’: an insight into Irish prospective secondary teachers' conceptual understanding of the division of fractions

Abstract: This paper reports on an investigation into the conceptual knowledge, through the domain of fraction division, of prospective secondary mathematics teachers in their final/fourth year of undergraduate initial teacher education. The aim of the study is to assess if levels of conceptual knowledge in this domain are sufficient in order for these prospective teachers to teach for understanding. Some impact of conceptual understanding on teaching approaches is also explored. The content of the teacher education pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…PSTs' understanding the meaning of a fraction as a part of whole leads them to some difficulties to explain the tasks on HTT 2. Some of them did not realise other interpretations for those task such measurement (or quotitive meaning), partitive meaning, and product and factors (Alenazi, 2016;Ball, 1990;Ma, 1999;Putra, 2016Putra, , 2019Slattery & Fitzmaurice, 2014). Some potential didactical techniques such as τd4, constructed directly from their mathematical knowledge, tend to be neglected because they consider that it is too abstract for the pupils.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…PSTs' understanding the meaning of a fraction as a part of whole leads them to some difficulties to explain the tasks on HTT 2. Some of them did not realise other interpretations for those task such measurement (or quotitive meaning), partitive meaning, and product and factors (Alenazi, 2016;Ball, 1990;Ma, 1999;Putra, 2016Putra, , 2019Slattery & Fitzmaurice, 2014). Some potential didactical techniques such as τd4, constructed directly from their mathematical knowledge, tend to be neglected because they consider that it is too abstract for the pupils.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Previous studies on how teachers deal with multiplication and division of rational numbers also show that teachers may succeed to solve operations of fractions themselves but still be unable to explain the reasons behind the used techniques (Alenazi, 2016;Ball, 1990;Erdem, Gökkurt, Sahin, Basibüyük, & Soylu, 2015;Ma, 1999;Putra, 2016Putra, , 2019Slattery & Fitzmaurice, 2014). Ma (1999) found that the U.S. teachers had various misconceptions about the meaning of division by fractions.…”
Section: Teachers' Knowledge Of Operations With Rational Numbersmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it is understandable that the situation was more challenging from a mathematical point of view, considering that the literature indicates gaps in teaching knowledge about the division of fractions (Bayoud, 2011;Özel, 2013;Slattery & Fitzmaurice, 2014). Moreover, historically the contents of basic education (and its justifications) have lacked a systematic approach during initial training, with articulations between theory and practice, between school and academic mathematics, productively for teaching demands (Santos, 2005;Fürkotter & Morelatti, 2007;Nacarato & Passos, 2007;Moriel Junior & Cyrino, 2009;Fiorentini et al, 2016;Crecci et al, 2017).…”
Section: Map Of Connections Of Specialised Knowledge In the Situation Of Answering To A Student Why He/she Should Invert-and-multiply To mentioning
confidence: 99%
“…In these situations, the teacher should not only know the mathematical justification itself but also know how to teach it respecting the student's level (Peterson, 1972;Lorenzato, 1993;Nobre, 1996;Moriel Junior & Wielewski, 2013;Leikin et al, 2017). However, there are indications that there are usually gaps in knowledge and teacher education (Lorenzato, 1993;Fiorentini, 2005;Santos, 2005;Angelo et al, 2009), and often the teachers have the same difficulties as the students (Bayoud, 2011;Özel, 2013;Slattery & Fitzmaurice, 2014).…”
Section: Introductionmentioning
confidence: 99%